A trauma-informed substance use disorder prevention program for transracially adopted children and adolescents. (August 2022) - Baden, Amanda L.; Sharma, Sunanda M.; Balducci, Samantha; Ellis, Lisa; Randall, Rebecca; Kwon, DaYeon; Harrington, Elliotte S.
Abstract: The prevalence of substance use among transracial and international adoptees is higher than that of non-adopted persons, and yet no specialized treatment modalities exist for this underserved population. Our purpose is to propose a substance use disorder (SUD) prevention program for transracial adoptive families that addresses the specific issues that face this community. There are several pre- and post-adoption factors which position transracial and international adoptees (TRIAs) to be at higher risk to develop SUDs. Some of these factors include adoption identity, trauma, loss, genetics, and racial discrimination. The biopsychosocial (BPS) model (Engel, 1977) is used to conceptualize SUDs in adoptees, and theories that focus on adoption-related development issues such as the Adoptee Stress and Coping Model (Brodzinsky, 1990) are also presented. Our proposed program, Strengthening Transracial Adoptive Families (STAF), utilizes the Guiding Good Choices (GGC) prevention program as its foundation to integrate a culturally responsive adoption-focused curriculum to best serve transracial adoptive families.